Health Communication in the Changing Media Landscape Perspectives from Developing Countries - Vemula, Ravindra Kumar; Gavaravarapu, SubbaRao M.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
'This book is 'new' and 'original'. It moves away from traditional thinking in the health communication field. It presents perspectives from countries and societies which are often not covered in 'mainstream' collections. It deserves to be read by both scholars and practitioners alike' - Jan Servaes, UNESCO Chair in Communication for Sustainable Social Change This book advances new understandings of how technologies have been harnessed to improve the health of populations; whether the technologies really empower those who use information by providing them with a choice of information; how they shape health policy discourses; how the health information relates to traditional belief systems and local philosophies; the implications for health communicators; how certain forms of silence are produced when media articulates and problematizes only a few health issues and sidelines others; and much more. The book brings together current research and discussions on the three areas of policy, practices and theoretical perspectives related to health communication approaches in developing countries, presenting well-researched and documented essays that will prove helpful for academic and scholarly inquiry in this area.
INTRODUCTION -- PART I.HEALTH COMMUNICATION: DISCOURSES FROM TRADITION TO MODERNITY -- 1.Witchcraft and the moral philosophy of Ubuntu are entangled: Implications for HIV & AIDS communication in South Africa. Colin Chasi -- 2.Communicable and non-communicable diseases and health communication in mainland China and Hong Kong. Patchanee Malikhao -- 3.Sexual health in changing media scenarios in Russia. Elizaveta Golousova & Dmitry Strovsky -- PART II.HEALTH COMMUNICATION IN THE CHANGING MEDIA LANDSCAPE -- 4.Digital technology and HIV & AIDS prevention in Kenya. Nancy Muturi -- 5.The role of mHealth in India: Understanding the futuristic ramifications for community empowerment. Ravindra Kumar Vemula -- 6.Media and public health communication at the grassroots: Village cinemas and HIV education in Papua New Guinea. Verena Thomas & Mark Eby -- PART III.FRAMING OF HEALTH IN MEDIA -- 7.No news is bad news: examining the discourse around Hugo Chávez's illness. Carolina Acosta-Alzuru -- 8.The forms of silence: Media coverage on neglected diseases in Brazil. Raquel Paiva and and Igor Sacramento -- 9.Of bulging bellies and slimming TVs: Television and nutrition transition in India. SubbaRao M Gavaravarapu -- PART IV.EMERGING ISSUES -- 10.Exploring individual, cultural and structural components of health communication programs: A gender integrative approach. Saumya Pant, Manisha Pathak-Shelat, Aanchal Sharma & Pradeep Krishnatray -- 11.Covering the last mile: A challenge in health communication in India? Arbind Sinha -- CONCLUSION .
Keywords: Economic development; Culture-Study and teaching; Civilization-History.; Media and Communication; Communication Studies; Regional Development; Public Health